PEMAHAMAN TENTANG EKOLITERASI DAN PERSEPSI KELOMPOK SADAR WISATA (POKDARWIS) TERHADAP IMPLEMENTASI CHSE (CLEAN, HEALTH, SAFETY & ENVIROMENTAL SUSTAINABILITY) DI KAWASAN GEOPARK GLOBAL CILETUH PALABUHANRATU - Ahmad Yani; Asep Mulyadi; Rosita Rosita (Geography Education Study Program, Universitas Samudra, 2022)
Ciletuh Palabuhanratu is a tourist destination area that has received a UNESCO Geopark certificate. However, the people in it still lack awareness and concern for cleanliness, health, safety, and the environment. Therefore, it is necessary to raise awareness and concern for the environment. The application of environmental awareness in the CHSE (Clean, Health, Safety & Environmental Sustainability) program needs to be carried out in every tourism service unit through the Tourism Awareness Group (Pokdarwis). The question posed in this research is how is the perception of Pokdarwis members and the community towards the implementation of CHSE in the Ciletuh Palabuhanratu Geopark Area? The method used is a survey with 90 respondents. The results showed that the perception of Pokdarwis members and the community towards the implementation of CHSE was relatively good. Researchers recommend making strict rules to maintain environmental sustainability and security in the Ciletuh Palabuhanratu Global Geopark Area.